2020
DOI: 10.1051/0004-6361/202038511
|View full text |Cite
|
Sign up to set email alerts
|

The GAPS Programme at TNG

Abstract: Context. The detailed chemical composition of stars is important in many astrophysical fields, among which is the characterisation of exoplanetary systems. Previous studies seem to indicate an anomalous chemical pattern of the youngest stellar population in the solar vicinity that has sub-solar metal content. This can influence various observational relations linking the properties of exoplanets to the characteristics of the host stars, for example the giant planet-metallicity relation. Aims. In this framework… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
19
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 100 publications
6
19
0
Order By: Relevance
“…It has been observed that strong ionised lines of Fe, Ti, and Cr yield large abundances in young and cool (T eff < 5400 K) stars (see e.g. D 'Orazi et al 2009;Schuler et al 2010;Tsantaki et al 2019;Baratella et al 2020a). This is referred to as the ionisation balance problem.…”
Section: Behaviour Of Spectral Linesmentioning
confidence: 99%
“…It has been observed that strong ionised lines of Fe, Ti, and Cr yield large abundances in young and cool (T eff < 5400 K) stars (see e.g. D 'Orazi et al 2009;Schuler et al 2010;Tsantaki et al 2019;Baratella et al 2020a). This is referred to as the ionisation balance problem.…”
Section: Behaviour Of Spectral Linesmentioning
confidence: 99%
“…Carbon abundances were derived by spectral synthesis of the CH molecular band at 430 nm using the CH line list provided in Masseron et al (2014). These abundances are expressed relative to the solar value obtained in Baratella et al (2020). Oxygen abundances were derived by spectral fitting of the [O I] 630 nm line.…”
Section: Stellar Parameters and Chemical Abundances Of The Fgk Primariesmentioning
confidence: 99%
“…NGC 2682 (M67) -This is one of the most studied open clusters and has solar metallicity and age (see e.g. Bertelli Motta et al 2018;. We observed four stars, two on the red clump and single, and two red giants known to be binary systems (see Tables 2 and 5).…”
Section: Comparison With Literaturementioning
confidence: 83%
“…In this case two stars are in common with our sample, as they were targeted on purpose. However, only one (Tombaugh 5_1 for us, 7701 in Baratella et al 2018) is analyzed in both papers, as they considered the second (Tombaugh 5_2 for us, 8099 in Baratella et al 2018) a possible non member on the basis of its RV and previous literature. The latter star has a high probability of be-ing a member according to and the RVs measured by us and Gaia RVS upport its membership.…”
Section: Comparison With Literaturementioning
confidence: 99%
See 1 more Smart Citation